Efficacy of various regimens of bioactive marine fish concentrate, glucosamine sulfate, and chondroitin sulfate in treating knee osteoarthritis - D.G. Rekalov; I.O. Daniuk; R.L. Kulinich; T.M. Tarasenko; E.Yu. Samofal; O.Ye. Akimov; V.O. Kostenko (Bolʹ, Sustavy, Pozvonočnik)
Background. Osteoarthritis (OA) is one of the most common joint diseases worldwide. The search for effective treatment regimens to reduce symptoms and improve joint function is essential. The purpose was to compare the effectiveness of different regimens of bioactive marine fish concentrate (BMFC) in the treatment of knee OA with oral glucosamine sulfate (GS) and chondroitin sulfate (CS). Materials and methods. The study involved 60 patients with stage II knee OA. The patients were divided into three groups: the first group received 1 ml of BMFC daily (20 injections), the second group received 2 ml every other day (10 injections), and the third group received GS and CS in tablet form. Clinical efficacy was assessed using the WOMAC scale on days 3, 7, 14, and 21. Results. In the group that received BMFC daily, pain decreased by 41.4 % on day 7 and by 58.7 % on day 21. Joint stiffness decreased by 51.9 %, and range of motion increased by 51.3 %. In the group receiving 2 ml of BMFC every other day, pain reduction was 37.1 % on day 7 and 55.7 % on day 21. Joint stiffness decreased by 49.2 %, and range of motion improved by 46.0 % by the end of treatment. Both BMFC groups demonstrated similar efficacy. Patients receiving GS and CS showed less pronounced improvements. Conclusions. Injectable BMFC demonstrated higher efficacy in treating OA compared to oral GS and CS. Both BMFC administration regimens (daily administration of 1 ml and administration of 2 ml every other day) proved effective in reducing pain, alleviating joint stiffness, and improving functional capacity. The 2 ml every-other-day regimen achieved comparable efficacy with fewer injections, enhancing convenience and improving adherence to therapy.